2022
DOI: 10.1101/2022.10.29.514383
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A multi-omics analysis of glioma chemoresistance using a hybrid microphysiological model of glioblastoma

Abstract: Chemoresistance is a major clinical challenge in the management of glioblastoma (GBM) Temozolomide (TMZ) is the chemotherapeutic drug of choice for GBM; however, the therapeutic effect of TMZ is limited due to the development of resistance. Recapitulating GBM chemoresistance in a controlled environment is thus essential in understanding the mechanism of chemoresistance. Herein, we present a hybrid microphysiological model of chemoresistant GBM-on-a-chip (HGoC) by directly co-culturing TMZ-resistant GBM spheroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 158 publications
0
2
0
Order By: Relevance
“…However, cell flux is mainly generated according to the interplay between diffusive and adhesive forces, and the directional motion due to chemotaxis. As observed in experimental studies, when cell-cell adhesive forces are dominant, tumors are able to maintain their compact structure, while highly invasive tumors could exhibit a long trace of cell migration [40]. In addition, the composition of the ECM surrounding the tumor is an important stimulus that may switch the invasion mode [14].…”
Section: Model Formulationmentioning
confidence: 99%
“…However, cell flux is mainly generated according to the interplay between diffusive and adhesive forces, and the directional motion due to chemotaxis. As observed in experimental studies, when cell-cell adhesive forces are dominant, tumors are able to maintain their compact structure, while highly invasive tumors could exhibit a long trace of cell migration [40]. In addition, the composition of the ECM surrounding the tumor is an important stimulus that may switch the invasion mode [14].…”
Section: Model Formulationmentioning
confidence: 99%
“…GBM-neuron synaptic interactions in TME have a pivotal role in tumor growth and invasion [36]. We have recently shown that these interactions significantly change the secretome profile of inflammatory and invasion cytokines [37]. More interestingly, the variation in cytokine profile strongly depends on the state of hGBM cells (i.e., non-resistant or TMZresistant) and plays a dual effect.…”
Section: Introductionmentioning
confidence: 99%